Low versus adequate carbohydrate diet in Brazilian jiu-jitsu athletes: comparisons of hormonal biomarkers, physical and psychological - Maynard, D. d. C.; Matos , R. C.; Damasceno, I. C.; Brito, C. J.; Miarka, B.; Grigoletto, M. E. d. S.; Mendes-Netto, R. S. (Archives of Budo, 2018)
Background and Study Aim: One of the strategies for rapid weight loss among combat sports athletes is calorie restriction with consequent reduction of carbohydrate, which despite its efficacy has been an area of controversy. This study aim is the effects of a low carbohydrate diet on body composition, hormonal profiles and performance task in Brazilian jiu-jitsu (BJJ) athletes.